Integrated planning for a global pharmaceutical supply chain: an ambidexterity perspective - Mahsa Yousefi Sarmad; Mir Saman Pishvaee; Hamed Jahani; Seyed Mohammad Sadegh Khaksar; Dmitry Ivanov (Annals of Operations Research, 2023)
Based on the concept of ambidexterity, we develop a multi-objective, multi-product, and multi-period model to integrate planning for research and development (R&D) and production and distribution (P&D) in a global pharmaceutical supply chain (PSC) considering delays in the entire supply chain. We also propose robust possibilistic programming (RPP) approach to deal with the epistemic uncertainty of some critical input parameters. Applying the ambidexterity approach that emphasizes optimizing a balanced framework based on the R&D and P&D planning, our study reconciles the explorative and exploitative supply chain strategies in the context of global PSCs. The proposed integrated model can manage the inherent delays and uncertainties in the R&D processes and P&D systems via a novel, credibility-based, robust possibilistic programming model. We illustrate the application of our model using a real-world case study of one of the largest and most reputable pharmaceutical companies in Iran. The results affirm the credibility and feasibility of the proposed model when juxtaposed with a non-integrated model. Our study suggests the use of ambidexterity approach in resource allocation planning, risk management, and enhancement of performance in sophisticated settings such as global PSCs.
Keywords: 000; Pharmaceutical supply chain; Global supply chain; Research and development (R&D); Production and distribution; Robust possibilistic programming; Ambidexterity